Analisis Perbedaan Usia Ibu Hamil dan Tingkat Kepatuhan Konsumsi Tablet Ferrum (Fe) pada Ibu Hamil yang Anemia dan Tidak Anemia - Triandini, Ni Komang Yulita; Suratiah, Suratiah; Runiari, Nengah; Hartati, Ni Nyoman (Jurnal Gema Keperawatan, 2023)
Anemia experienced by pregnant women will hurt the mother during pregnancy until the postpartum period and also the fetus.The highest incidence of anemia in pregnant women in Badung Regency is occupied by the South Kuta Health Center with a percentage of 27.0%. This study aims to determine differences in the age of pregnant women and the level of compliance with the consumption of Fe tablets in pregnant women who are anemic at the South Kuta Health Center in 2023. This research uses a case control design. The sample selection used a purposive sampling technique, namely 88 respondents who were divided into 2 groups, 44 respondents in the group of anemic mothers and 44 respondents in the groups of non-anemics mothers. The data collection tool is the MMAS-8 questionnaire. The data were analyzed using the Chi-Square test, with the results of the study showingthat there was a difference in age between pregnant women who were anemic and who were not anemic, obtaining a p value = 0.007 (p 0.05) with an Odds Ratio value of 11.057. In the variable level of compliance with the consumption of Fe tablets, the p value = 0.000 can be concluded that there is a difference in the level of compliance with the consumption of Fe tablets in pregnant women who are anemic and who are not anemic with an Odds Ratio value of 0.022. In this study it can be concluded that there are differences in the age of pregnant women and the level of compliance with the consumption of Fe tablets in pregnant women who are anemic and who are not anemic.